An Overview of Postpartum Mothers’ Knowledge Regarding Exclusive Breastfeeding at Pahandut Primary Health Center - Wei, Ling Ling; Arisani, Greiny (CV. Social Politic Genius (SIGn), 2024)
The low knowledge of postpartum mothers in providing exclusive breastfeeding at the Pahandut PHC was identified as the suspected root cause. This quantitative descriptive study aimed to map the overview of the knowledge level of postpartum mothers regarding exclusive breastfeeding in the area. The study employed a cross-sectional approach using a total sampling technique on 55 postpartum mothers at the Pahandut PHC. Primary data were collected using a 21-item questionnaire and analyzed univariately. The results showed that the respondents’ knowledge levels were distributed across ‘sufficient’ (n = 28; 50.90%), ‘good’ (n = 16; 29.10%), and ‘poor’ (n = 11; 20.00%). The majority of mothers with sufficient knowledge were aged 20–25 years (69.09%), had 2–4 children (53.33%), had secondary education (66.67%), were unemployed (54.00%), did not receive family support (47.06%), and received health worker support (47.73%). Urgent interventions are required to correct specific misconceptions and retrain support providers, both families and health workers, to increase exclusive breastfeeding coverage.